Synthesis and crystallographic characterisation of pyridyl- and indoleninyl-substituted pyrimido[1,2-b]indazoles - Ramle, Abdul Qaiyum; Tan, Sang Loon*; Tiekink, Edward R. T. * (MDPI, 2022)
Pyridyl- and indoleninyl-substituted pyrimido[1,2-b]indazole were synthesised in good to high yields from the condensation reaction of 1,3-dialdehydes with 3-aminoindazoles. The structural features of the compounds were determined by NMR (1H, 13C and 19F), FT-IR and HR-MS. The spectroscopic assignments were confirmed by X-ray crystallography for two derivatives, i.e., 9-Bromo-3-(pyridin-4-yl)pyrimido[1,2-b]indazole (1b) and 10-Methoxy-3-(pyridin-4-yl)pyrimido[1,2-b]indazole (1c), which further provides support for significant delocalisation of π-electron density over the entire fused ring system. The molecular packing was assessed by conventional methods together with Hirshfeld surface analyses. In 1b, the molecular packing features pyrimidyl-N–H···N(pyrimidyl), π(pyrazolyl)···π(pyrimidyl) and Br···N interactions within a two-dimensional array. In 1c, pyrimidyl-C–H···N(pyrazolyl) and pyridyl-C–H···O(methoxy) interactions feature within a three-dimensional architecture.